ADMISSION OF DEMOCRATIC REPUBLIC OF CONGO (DRC) IN THE EAST AFRICAN COMMUNITY (EAC): ARE THERE OPPORTUNITIES FOR KENYA? - Moses, Mugwe (International Journal of Innovative Technologies in Social Science, 2022)
Many countries across the globe are adopting regional economic integration as a strategy towards speeding economic growth and development. Through these integrations, there has been a surge in regional economic blocks, which have served to expand the market for many countries and open others to more robust trading activities and international business. East African Community has also been expanding its membership from three-member states to seven member states. This expansion has been aimed at enhancing the effectiveness of the integration and making the community more comprehensive for the benefit of member countries. The inclusion of Democratic Republic of Congo as the seventh member country was recently concluded, and this has been viewed in varied dimensions. However, there has been a debate on whether the inclusion of DRC will enhance the benefits by the member countries or not. This paper, therefore, sought to establish the opportunities for international business that the EAC member countries are likely to gain out of the inclusion of DRC. The study singled out Kenya, as the largest economy in the community and at the centre of the admission of DRC into the EAC. An empirical approach was adopted where key reports, existing literature and reviews have been reviewed to come up with the findings and discussions. The results have portrayed that the inclusion of DRC into the EAC increases the community’s market by over 89 million consumers while opening the EAC to the Pacific Ocean. Kenyan multinationals have also been steadfast in investing in DRC upon admission of the country into DRC. The results have shown that while regional economic integration may come up with a share of problems from member countries, especially unstable countries, it also opens opportunities for established economies to invest in such economies for continued economic growth and development. It is recommended that both DRC and Kenyan governments lays out more trade facilitation policies and strategies in order to encourage international trade between the two countries and across the EAC region.